2018
DOI: 10.2196/humanfactors.9371
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Misses and Near Misses Related to Multitasking on the Electronic Health Record: Observational Study and Qualitative Analysis

Abstract: BackgroundClinicians’ use of electronic health record (EHR) systems while multitasking may increase the risk of making errors, but silent EHR system use may lower patient satisfaction. Delaying EHR system use until after patient visits may increase clinicians’ EHR workload, stress, and burnout.ObjectiveWe aimed to describe the perspectives of clinicians, educators, administrators, and researchers about misses and near misses that they felt were related to clinician multitasking while using EHR systems.MethodsT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Other studies have also reported that IT adoption increases the quality of patient care and improves the standards in healthcare organizations [ 6 ] by supporting clinicians in making clinical decisions efficiently [ 22 – 24 ]. Moreover, it reduces the risk of making errors by decreasing the clinicians’ cognitive workload, synthesizing and organizing information in accessible and usable formats [ 25 ]. IT improves providers’ performance by reducing delays in care at the time of shift change and maintains continuity of care [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also reported that IT adoption increases the quality of patient care and improves the standards in healthcare organizations [ 6 ] by supporting clinicians in making clinical decisions efficiently [ 22 – 24 ]. Moreover, it reduces the risk of making errors by decreasing the clinicians’ cognitive workload, synthesizing and organizing information in accessible and usable formats [ 25 ]. IT improves providers’ performance by reducing delays in care at the time of shift change and maintains continuity of care [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, “facilitating the communication management in the technological environment” along with its subcategories was identified as another perceived benefit for IT. Similarly, two studies maintained that IT improved communication between/among wards and staff [ 23 , 27 ], teamwork and team support [ 25 ]. A systematic review on this topic reported several themes, including the impact of EHR on information exchange between patients and clinicians; maintaining positive relationships, and partnering with patients; and the EHR as an amplifier of existing communication behaviors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Without approaches to manage these pressures, the situation may become untenable and result in decreased quality of care and physician burnout. 12,13 Reducing clinic inefficiencies can help physicians manage these pressures. For example, ophthalmology clinics generally maximize efficiency by using multiple exam rooms and ancillary staff, so that patients are examined during multiple stages (e.g., before and after dilation of eyes, before and after ophthalmic imaging studies).…”
Section: Précismentioning
confidence: 99%
“…Meanwhile, multitasking EHR use comprised almost half of medication reconciliation time, a higher proportion of time than in the visits as a whole [ 17 ]. Many clinicians may not believe they are multitasking when updating the EHR medication list while talking to patients because both tasks are concordant with the goals of reconciling medications [ 36 ]. However, research in cognitive psychology suggests that the act of reading or entering computer data while listening or talking with another person may increase both the risk of errors and the time required to complete each task [ 16 ].…”
Section: Discussionmentioning
confidence: 99%